Money attitude of Ukrainian young people: socio-demographic aspect - SIMKIV, MARIANNA (Journal of Education Culture and Society, 2020)
The article provides the results of research on how social and demographic peculiarities in uence money attitudes of Ukrainian youth. It reveals dependency on money attitudes on such characteristics as gender, age, education, place of residence, place of employment, employment position and income level.